FOYDALANUVCHI TOMONIDAN ANIQLANGAN BERILGANLAR TURLARI (UBS Scientific Bulletin, 2025)
The purpose of this article is to explain the importance of analyzingalgorithms, their definitions, relationships, and solving as many problems aspossible.